2017
DOI: 10.1111/gcb.13855
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of insects and droughts to growth decline of trembling aspen mixed boreal forest of western Canada

Abstract: Insects, diseases, fire and drought and other disturbances associated with global climate change contribute to forest decline and mortality in many parts of the world. Forest decline and mortality related to drought or insect outbreaks have been observed in North American aspen forests. However, little research has been done to partition and estimate their relative contributions to growth declines. In this study, we combined tree-ring width and basal area increment series from 40 trembling aspen (Populus tremu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 101 publications
(149 reference statements)
2
35
1
Order By: Relevance
“…Importantly, we found that the temporal trends in net above‐ground biomass change varied spatially along the gradient of the long‐term average of climate moisture availability, with a pronounced temporal decrease in the dry plots, due to a stronger temporal increase in mortality than an increase in growth. Our results indicated that although rising CO 2 , warming and associated increases in growing season length could increase tree growth in boreal forests (Girardin, Bouriaud, et al., ; Pretzsch et al., ), these positive climate change drivers for growth could be constrained by limited water availability (Chen et al., ; Hogg et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Importantly, we found that the temporal trends in net above‐ground biomass change varied spatially along the gradient of the long‐term average of climate moisture availability, with a pronounced temporal decrease in the dry plots, due to a stronger temporal increase in mortality than an increase in growth. Our results indicated that although rising CO 2 , warming and associated increases in growing season length could increase tree growth in boreal forests (Girardin, Bouriaud, et al., ; Pretzsch et al., ), these positive climate change drivers for growth could be constrained by limited water availability (Chen et al., ; Hogg et al., ; Wang et al., ).…”
Section: Discussionmentioning
confidence: 74%
“…In dry plots, warming had strong negative effects on net biomass change due to increased mortality and reduced growth. These negative effects of warming could reflect the coupling influences of direct heat stress and increased activity of insects (Allen et al., ; Anderegg et al., ; Chen et al., ; Hogg et al., ). With temporally decreasing climate moisture availability, which resulted from temporally increasing PET despite slightly increasing precipitation in the study area (Luo & Chen, ), net biomass change decreased in dry plots, due to a decrease in growth and an increase in mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5) and drought intensity during the summer of the previous year (Fig. It has also been reported that FTC outbreaks are triggered by above-average early spring temperatures (Ives 1973, Chen et al 2018. In contrast, previous studies have tended to stress that outbreaks may be inhibited when low minimum temperatures lead to high mortality of eggs in winter or starvation of hatchlings in spring due to frost damage to foliage (Blais 1955, Cooke andRoland 2003).…”
Section: Cyclicity Of Outbreaks Through Timementioning
confidence: 93%